A esclerose múltipla em uma abordagem metabolômica untargeted por espectrometria de massas - Leite, Fernando Brunale Vilela De Moura [UNIFESP] (2019)
Multiple sclerosis (MS) is a chronic autoimmune chronic inflammatory neurological disease of the central nervous system (CNS) that attacks the myelin sheath causing its destruction to varying degrees. The cause of MS is unknown and the most accepted theory involves combining genetic susceptibility with a non-genetic trigger in addition to a conducive immune system and contributing factors in the CNS. There is still no biological marker capable of detecting MS or predicting the prognosis of the disease or its clinical evolution. There are several possible biomarkers, but they still remain clinically relevant and none have the sensitivity and reliability to diagnose MS and monitor the course of the disease. The objective of clinical research in the area of demyelinating diseases and mainly MS is to find biomarkers that make it possible to evidence subclinical disease, disease activity or allow evaluation of treatment. This study analyzed by mass spectrometry cerebrospinal fluid (CSF) metabolic aspects in patients with suspected and confirmed diagnosis of Multiple Sclerosis with the objective and to discover a biomarker able to differentiate non-diseased persons from people diagnosed with multiple sclerosis in addition to being able to differentiate different classifications of multiple sclerosis. The untarget analysis performed demonstrated that there are viable means of differentiating patients with multiple sclerosis from normal individuals in addition to differentiating patients from different MS types. Through the analysis by PCA, PLS-DA, VIP and Heat map, it was possible to evidence a possible candidate for biomarker. This biomarker candidate is already cited in the literature. However, there are still few studies that show the mechanism and the relationship of decreased phosphatidylcholine levels in CSF samples. It is believed that the levels of this potential biomarker is directly related to the increased age of affected patients.